Working backwards : insights, stories, and secrets from inside Amazon - Bryar, Colin, ....-; Carr, Bill, 1967- (New York : St. Martin's Press, 2021)
"Working Backwards is an insider's breakdown of Amazon's approach to culture, leadership, and best practices from two long-time, top-level Amazon executives. Colin started at Amazon in 1998; Bill joined in 1999. In Working Backwards, these two long-serving Amazon executives reveal and codify the principles and practices that drive the success of one of the most extraordinary companies the world has ever known. With twenty-seven years of Amazon experience between them, much of it in the early aughts-a period of unmatched innovation that brought products and services including Kindle, Amazon Prime, Amazon Studios, and Amazon Web Services to life-Bryar and Carr offer unprecedented access to the Amazon way as it was refined, articulated, and proven to be repeatable, scalable, and adaptable. With keen analysis and practical steps for applying it at your own company-no matter the size-the authors illuminate how Amazon's fourteen leadership principles inform decision-making at all levels and reveal how the company's culture has been defined by four characteristics: customer obsession, long-term thinking, eagerness to invent, and operational excellence. Bryar and Carr explain the set of ground-level practices that ensure these are translated into action and flow through all aspects of the business. Working Backwards is a practical guidebook and a corporate narrative, filled with the authors' in-the-room recollections of what "Being Amazonian" is like and how it has affected their personal and professional lives. They demonstrate that success on Amazon's scale is not achieved by the genius of any single leader, but rather through commitment to and execution of a set of well-defined, rigorously-executed principles and practices-shared here for the very first time"--
Building blocks : leadership principles and mechanisms -- Hiring : Amazon's unique bar raiser process -- Organizing : separable, single-threaded leadership -- Communicating : narratives and the six-pager -- Working backwords : start with the desired customer experience -- Metrics : manage your inputs, not your outputs -- Kindle -- Prime -- Prime Video -- AWS -- Conclusion: Being Amazonian beyond Amazon.
Includes bibliographical references and index.
Keywords: Amazon.com (Firm) -- Management; Corporate culture; Decision making; E-commerce -- Management; Leadership; Success in business